173k views
3 votes
Simplify by combining like terms -6x equals 12 + 8y + 16x

User Mugx
by
5.4k points

1 Answer

4 votes

Answer:

The simplified expression is 22 x + 8 y + 12 = 0

Explanation:

Here, the given expression is : - 6x = 12 + 8y + 16 x

Like Terms: The terms which have the same coefficient variable in any given expression are called Like Terms.

In the given expression the only pair of like terms is (-6 x, and 16 x)

Solving the given expression , we get:

- 6x = 12 + 8y + 16 x

⇒12 + 8y + (16 x + 6 x) = 0

or, 12 + 8 y + 22 x = 0

Hence, the simplified expression is 22x +8y + 12 = 0

User Shaneek
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.